The impact of bariatric and metabolic surgery on cancer development - Lunger, Fabian; Aeschbacher, Pauline; Nett, Philipp C.; Peros, Georgios (Frontiers in Surgery, 2022)
Obesity (BMI ≥ 30 kg/m2) with related comorbidities such as type 2 diabetes mellitus, cardiovascular disease, sleep apnea syndrome, and fatty liver disease is one of the most common preventable risk factors for cancer development worldwide. They are responsible for at least 40% of all newly diagnosed cancers, including colon, ovarian, uterine, breast, pancreatic, and esophageal cancer. Although various efforts are being made to reduce the incidence of obesity, its prevalence continues to spread in the Western world. Weight loss therapies such as lifestyle change, diets, drug therapies (GLP-1-receptor agonists) as well as bariatric and metabolic surgery are associated with an overall risk reduction of cancer. Therefore, these strategies should always be essential in therapeutical concepts in obese patients. This review discusses pre- and post-interventional aspects of bariatric and metabolic surgery and its potential benefit on cancer development in obese patients.